An update on clinical, pathological, diagnostic, and therapeutic perspectives of childhood leukodystrophies. (2nd January 2020) - Ashrafi, Mahmoud Reza; Amanat, Man; Garshasbi, Masoud; Kameli, Reyhaneh; Nilipour, Yalda; Heidari, Morteza; Rezaei, Zahra; Tavasoli, Ali Reza
ABSTRACT: Introduction : Leukodystrophies constitute heterogenous group of rare heritable disorders primarily affecting the white matter of central nervous system. These conditions are often under-appreciated among physicians. The first clinical manifestations of leukodystrophies are often nonspecific and can occur in different ages from neonatal to late adulthood periods. The diagnosis is, therefore, challenging in most cases. Area covered : Herein, the authors discuss different aspects of leukodystrophies. The authors used MEDLINE, EMBASE, and GOOGLE SCHOLAR to provide an extensive update about epidemiology, classifications, pathology, clinical findings, diagnostic tools, and treatments of leukodystrophies. Comprehensive evaluation of clinical findings, brain magnetic resonance imaging, and genetic studies play the key roles in the early diagnosis of individuals with leukodystrophies. No cure is available for most heritable white matter disorders but symptomatic treatments can significantly decrease the burden of events. New genetic methods and stem cell transplantation are also under investigation to further increase the quality and duration of life in affected population. Expert opinion : The improvements in molecular diagnostic tools allow us to identify the meticulous underlying etiology of leukodystrophies and result in higher diagnostic rates, new classifications of leukodystrophies based on genetic information, and replacement of symptomatic managements with more specific targeted therapies. Abbreviations: 4H: Hypomyelination, hypogonadotropic hypogonadism and hypodontia; AAV: Adeno-associated virus; AD: autosomal dominant; AGS: Aicardi-Goutieres syndrome; ALSP: Axonal spheroids and pigmented glia; APGBD: Adult polyglucosan body disease; AR: autosomal recessive; ASO: Antisense oligonucleotide therapy; AxD: Alexander disease; BAEP: Brainstem auditory evoked potentials; CAA: Cerebral amyloid angiopathy; CADASIL: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy; CARASAL: Cathepsin A–related arteriopathy with strokes and leukoencephalopathy; CARASIL: Cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy; CGH: Comparative genomic hybridization; ClC2: Chloride Ion Channel 2; CMTX: Charcot-Marie-Tooth disease, X-linked; CMV: Cytomegalovirus; CNS: central nervous system; CRISP/Cas9: Clustered regularly interspaced short palindromic repeat/CRISPR-associated 9; gRNA: Guide RNA; CTX: Cerebrotendinous xanthomatosis; DNA: Deoxyribonucleic acid; DSB: Double strand breaks; DTI: Diffusion tensor imaging; FLAIR: Fluid attenuated inversion recovery; GAN: Giant axonal neuropathy; H-ABC: Hypomyelination with atrophy of basal ganglia and cerebellum; HBSL: Hypomyelination with brainstem and spinal cord involvement and leg spasticity; HCC: Hypomyelination with congenital cataracts; HEMS: Hypomyelination of early myelinated structures; HMG CoA: Hydroxy methylglutaryl CoA; HSCT: Hematopoietic stem cell transplant; iPSC: Induced pluripotent stem cells; KSS: Kearns-Sayre syndrome; L-2-HGA: L-2-hydroxy glutaric aciduria; LBSL: Leukoencephalopathy with brainstem and spinal cord involvement and elevated lactate; LCC: Leukoencephalopathy with calcifications and cysts; LTBL: Leukoencephalopathy with thalamus and brainstem involvement and high lactate; MELAS: Mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke; MERRF: Myoclonic epilepsy with ragged red fibers; MLC: Megalencephalic leukoencephalopathy with subcortical cysts; MLD: metachromatic leukodystrophy; MRI: magnetic resonance imaging; NCL: Neuronal ceroid lipofuscinosis; NGS: Next generation sequencing; ODDD: Oculodentodigital dysplasia; PCWH: Peripheral demyelinating neuropathy-central-dysmyelinating leukodystrophy-Waardenburg syndrome-Hirschprung disease; PMD: Pelizaeus‐Merzbacher disease; PMDL: Pelizaeus-Merzbacher-like disease; RNA: Ribonucleic acid; TW: T-weighted; VWM: Vanishing white matter; WES: whole exome sequencing; WGS: whole genome sequencing; X-ALD: X-linked adrenoleukodystrophy; XLD: X-linked dominant; XLR: X-linked recessive